2002
DOI: 10.1002/1521-3773(20020802)41:15<2811::aid-anie2811>3.0.co;2-#
|View full text |Cite
|
Sign up to set email alerts
|

A Patterned TiO 2 (Anatase)/TiO 2 (Rutile) Bilayer‐Type Photocatalyst: Effect of the Anatase/Rutile Junction on the Photocatalytic Activity

Abstract: Semiconductor photocatalysts have recently attracted much interest because of their possible applicability to detoxification of environmental pollutants [1] and solar-energy conversion. [2] Among the photocatalysts, TiO 2 is believed to be the most promising presently known material because of its superior photoreactivity, nontoxicity, long-term stability, and low price. The photocatalytic activity of TiO 2 depends on various parameters, including crystallinity, impurities, surface area, and density of surfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
164
0
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 458 publications
(172 citation statements)
references
References 15 publications
5
164
0
3
Order By: Relevance
“…An analogous synergistic effect is also commonly observed between anatase and rutile phases [32][33][34][35] and is moreover experimentally supported by photodeposition experiments of Ag. 36 However, in the case of brookite-rich nanoparticles, this synergistic effect has not been observed before, as pure brookite showed higher photocatalytic activity than the brookite-rich nanoparticles (see Fig. 5(c) and (d)).…”
Section: View Article Onlinementioning
confidence: 73%
“…An analogous synergistic effect is also commonly observed between anatase and rutile phases [32][33][34][35] and is moreover experimentally supported by photodeposition experiments of Ag. 36 However, in the case of brookite-rich nanoparticles, this synergistic effect has not been observed before, as pure brookite showed higher photocatalytic activity than the brookite-rich nanoparticles (see Fig. 5(c) and (d)).…”
Section: View Article Onlinementioning
confidence: 73%
“…Recent studies have shown that photoactivity of P25 exceeds that of anatase in several reaction systems [41,42]. Previously, we have also reported that TiO 2 P25, which is a mixture of anatase and rutile phases exhibited higher efficiency of phenol, pyridine and 4-heptanone degradation compared to commercial anatase particles TiO 2 ST-01 and anatase obtained from titanium isopropoxide (TIP) and titanium butoxide (TBT) hydrolysis in aqueous phase [43,44].…”
Section: Discussionmentioning
confidence: 86%
“…3 shows the two typical models of charge transfer between anatase and rutile. Some literature results (Bickley et al, 1991;Kawahara et al, 2002;Wang, Bai et al, 2012) suggested that photogenerated electrons tend to transfer from anatase to rutile, because the conduction band (CB) of anatase is more negative than that of rutile ( Fig. 3(A)).…”
Section: Effect Of Crystal Phasementioning
confidence: 99%